Dengue infections in travellers - Wilder-Smith, Annelies (Paediatrics and international child health, 2013)
Dengue has been designated a major international public health problem by the World Health Organization (WHO). It is endemic in most tropical and sub-tropical countries, which are also popular tourist destinations. Travellers are not only at significant risk of acquiring dengue but they also contribute to its spread to non-endemic regions. Furthermore, they may serve as sentinels to alert the international community to epidemics in dengue-endemic regions. GeoSentinel, a global surveillance network, monitors all travel-related illnesses and estimates that dengue accounts for 2% of all illness in travellers returning from dengue-endemic regions. In fact, in travellers returning from South-east Asia, dengue is now a more frequent cause of febrile illness than malaria. Dengue-infected travellers returning home to countries where the vector exists can place the local population at risk of further spread of the disease with subsequent autochthonous cycles of infection. The true incidence of dengue amongst travellers may be underestimated because of variability in reporting requirements in different countries and under-diagnosis owing to the non-specific clinical presentation of the disease. Risk factors for acquiring dengue include duration of stay, season of travel and epidemic activity at the destination. Any pre-travel advice on the risks of developing dengue infections should consider these factors.